Operationalizing deliberate practice for performance improvement in sport - Ford, P. R.; Coughlan, E. K. (Skill acquisition in sport: research, theory and practice, 2020)
In this chapter, we briefly reviewed deliberate practice theory and research in sport. It appeared that coaches infrequently have athletes engage in deliberate practice as defined and shown by Ericsson et al. (1993). Therefore, we sought to operationalise deliberate practice in sport so that it can more easily be applied to athletes. We summarised how to create deliberate practice for athletes into the acronym ASPIRE (Analyse, Select, Practice, Include feedback and Repetition, Evaluate). ASPIRE requires analysis of current performance of experts in the sport and monitoring of one`s own current performance to determine key aspects within one`s repertoire that require improvement and how they can be improved. It requires the selection of a key aspect to be practiced and goal setting, before repetiti ve practice of that aspect in a representative environment with feedback. Further analysis is required to evaluate the success of the intervention. ASPIRE forms a key part of what we term a deliberate environment where all of the activities surrounding an athlete are goal-directed towards improving their future performance or recovery from previous performance. Given there are multiple options for activities that can be scheduled for athletes across time and only limited time, the use of these concepts can provide focus on which activities to schedule. We suggest selecting whenever possible and appropriate the activity that will lead to the largest amount of improvement in competition performance and its underlying attributes at that time.